Effect of post-harvest losses on profitability of rice (Oryza sativa) processors in Benue State, Nigeria - Dzahan, Hilary Liambee (Agribusiness Department, Agriculture and Forestry Faculty, Universitas Sulawesi Barat, Indonesia, 2025)
This study assessed the impact of post-harvest losses on the profitability of rice processors in Benue State, Nigeria. The objectives were to describe the socio-economic characteristics of rice processors, estimate the extent of post-harvest losses, and analyze their influence on profitability. A total of 150 rice processors were selected using a combination of purposive, multi-stage, and simple random sampling techniques, with Taro Yamane’s formula guiding the determination of the sample size. Data were analyzed using descriptive statistics, gross margin analysis, and Ordinary Least Squares (OLS) regression. Results showed that the average age of the processors was 41 years, with 47.33% being married and 74.67% having a formal education. Most processors (44.67%) handled between 7 and 10 bags of 100 kg weekly, and 36.67% had 10–15 years of processing experience. Inadequate drying facilities accounted for the highest post-harvest losses (61.56 kg or 25.60%), while pest and rodent damage contributed the least (30.14 kg or 12.53%). Gross margin analysis revealed an average gross income of ₦90,000 per 100 kg bag and a net farm income of ₦10,467. Regression analysis (adjusted R² = 0.59) identified key determinants of losses and profitability, with milling technology, labor, drying, and transportation showing significant adverse effects on losses. The scale of operation and rice prices significantly enhanced profitability. The study recommends investments in modern processing technologies, improved infrastructure, and training to reduce losses and boost profitability.